COVID-associated neuro-ophthalmopathy. Issues of diagnosis and treatment - Igor N. Stepanov; Elena V. Savchenko; Marina R. Kovaleva; Nikita Yu. Shalkin (LLC "MEDIAFORMAT", 2022)
Since the beginning of the COVID-19 pandemic, a large number of reports on extrapulmonary manifestations of the disease have appeared, sometimes focusing on complex cases and challenging diagnostic tasks. Neuroophthalmological manifestations of COVID-19 include opticoneuritis, acute transverse myelitis, viral encephalitis, toxic encephalopathy, leukoencephalopathy, acute disseminated encephalomyelitis and some other conditions. 30.8% of patients with neurological symptoms of COVID-19 have idiopathic intracranial hypertension. The breadth of the diagnostic search complicates the task of the doctor to choose right diagnostic measures and treatment tactics. This article presents the clinical observation of a patient with ophthalmopathy and idiopathic intracranial hypertension during the post-COVID period. The case deserves special attention in the context of differential diagnosis with autoimmune diseases. We also present current publications on the topic of ophthalmopathy of various etiologies, including a new coronavirus infection, focusing on its role in the development of ocular and neurological symptoms. The current epidemiological situation implies the mandatory consideration of infectious pathology during diagnostics search. Understanding the impact of COVID-19 on human organs and systems and timely diagnosis will help to reduce the time spent on ineffective treatment and expensive diagnostic measures.